An Overview of the Literature on the Relationship Between Social Media Influencers and the Health of Teenagers - Dr Nitu Singh Sisodia, Pooja Yadav, Dr. Bharti Meghani Mishra (South Eastern European Journal of Public Health, 2025)
Teenagers are increasingly getting their health information from social media influencers (SMIs). However, SMIs' lack of experience and business objectives provide problems for the health of adolescents. In order to better understand these issues, this scoping review sought to compile the body of knowledge about the role of SMIs in adolescent health. We filtered papers according to predetermined criteria after doing a thorough search of eight databases. Between 2012 and 2024, 51 articles were included in the final sample. The findings showed that SMIs were not consistently defined or categorized. Substance abuse, diet, and attractiveness were the most often discussed themes, although mental and sexual health issues were less prevalent. The reviewed research illuminated the possible advantages and difficulties for adolescent health by highlighting SMIs' capacity to build reliable relationships with their followers. The majority of research, however, concentrated on the detrimental effects of SMIs, including the encouragement of distorted body images, poor eating habits, drug abuse, and incorrect diagnosis and treatment recommendations. Another significant issue was the improper promotion of unhealthy goods (such as junk food, alcohol, and tobacco items). Stricter regulation as well as enhanced social media and health literacy were noted in the assessed research as key avenues for policy action. The possible benefits of SMIs and the best ways to incorporate them into health promotion initiatives received little attention. Furthermore, the vast majority of research was carried out.